Sekuritisasi Isu Kudeta Militer Myanmar Tahun 2021 oleh Indonesia terhadap Association Southeast Asian Nations (ASEAN) - Khairiah, Annisa; Muhammad Yusra; Rifki Dermawan (Hubungan Internasional Universitas Andalas, 2025)
On February 1, 2021, the military junta carried out a coup against the Myanmar government for alleged fraud in the November 2020 election which won Aung San Suu Kyi from the National Lead Democracy (NLD) Party. This coup directly impacted the security of Myanmar's neighboring countries and the international community, resulting in threats to the stability and sovereignity of ASEAN member states in Southeast Asia. This study aims to explain the stages of securitization carried out by Indonesia through President Joko Widodo and Indonesia Foreign Minister, Retno Marsudi, as part of ASEAN. These stages will be analyzed using the concept of securitization, which explains through two stages, raising the issue and convincing the audience. The method in this research uses qualitative method with descriptive approach that utilizes secondary data that has been found. This study found that President Joko Widodo and Indonesia Foreign Minister, Retno Marsudi securitized the issue against ASEAN member countries by making some efforts and giving various statements. These statements form an idea construction that the issue of Myanmar's military coup is a threat and requires collective emergency action. At the stage of raising the issue, Indonesia was the country that responded to the issue of the Myanmar military coup and was assisted by several functional actors outside the region. At the stage of convincing the audience, Indonesia held a bilateral meeting with the Prime Minister of Malaysia, a meeting with the Minister of Foreign Affairs of Myanmar, doing shuttle diplomacy and issued a series of statements to its audience. From this stage, it was found that Indonesia succeeded in legitimizing the issue of the Myanmar coup, thereby making ASEAN reach a consensus by holding the ASEAN Leader's Meeting (ALM) and forming five-point consensus. Keywords: Indonesia, Joko Widodo, Myanmar Military Coup, Retno Marsudi, Securitization.